Vascular Response During Mental Stress in Sedentary and Physically Active Patients With Obstructive Sleep Apnea - Ferreira-Silva, Rosyvaldo (J Clin Sleep Med, 2018)
STUDY OBJECTIVES: To compare vascular function of sedentary (SED) versus physically active (ACTIVE) patients with obstructive sleep apnea (OSA) during rest and mental stress. METHODS: Patients with untreated OSA without other comorbidities were classified into SED and ACTIVE groups according to the International Physical Activity Questionnaire. Blood pressure (BP), heart rate (HR), forearm blood flow (FBF) (plethysmography), and forearm vascular conductance (FVC = FBF / mean BP × 100) were continuously measured at rest (4 minutes) followed by 3 minutes of mental stress (Stroop Color Word Test). RESULTS: We studied 40 patients with OSA (men = 24, age = 50 ± 1 years, body mass index = 29.3 ± 0.5 kg/m(2), apnea-hypopnea index = 39.3 ± 4 events/h). Leisure time physical activity domain in SED (n = 19) and ACTIVE (n = 21) was 20 ± 8 and 239 ± 32 min/wk, (P < .05). Baseline profile and perception of stress were similar in both groups. Baseline FBF (3.5 ± 0.2 mL/min/100 mL versus 2.4 ± 0.14 mL/min/100 mL) and FVC (3.5 ± 0.2 U versus 2.3 ± 0.1 U) were significantly lower in the SED group than in the ACTIVE group, respectively (P < .05). HR and BP increased similarly during mental stress test in both groups. Changes during mental stress in FBF (0.65 ± 0.12 versus 1.04 ± 0.12) and FVC (0.58 ± 0.11 versus 0.99 ± 0.11) were significantly lower in the SED group than in the ACTIVE group, respectively (P < .05). There was a significant correlation between leisure time physical activity and FBF (r = .57, P < .05) and FVC (r = .48, P < .05) during mental stress. CONCLUSIONS: The vascular response among patients with OSA is influenced by the level of physical activity. A high level of physical activity may partially protect against the cardiovascular dysfunction associated with OSA. CITATION: Ferreira-Silva R, Goya TT, Barbosa ER, Durante BG, Araujo CE, Lorenzi-Filho G, Ueno-Pardi LM. Vascular response during mental stress in sedentary and physically active patients with obstructive sleep apnea. J Clin Sleep Med. 2018;14(9):1463–1470.